FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Sari, Riani Dwi Indah (JURNAL MEDIA KESEHATAN, 2018)
Pneumonia is one of the causes of infant mortality. The percentage of pneumonia in Indonesia in 2009 increased (49.23%) and in 2010, falling to (39.38%) of the number of infants in Indonesia. In as many as 16.401 cases of Bengkulu province. The high incidence of pneumonia were found in 214 cases Curup health center. The purpose of this study determine the relationship of the factors associated with the incidence of pneumonia in infants Curup Work Area Health Center in 2013. This study used a case-control method with a number of 38 samples were taken in total control sampling and 38 samples were taken by simple random sampling. The place and time of the study, in Curup Health Center in January 2014. Retrieval of data using a data collection sheet was analyzed using Chi-square. Univariate analysis showed almost all of the infants (89.5%) did not LBW, most of the infants (65.8%) had complete immunization status and most of the infants (68.4%) were exclusively breastfed. In bivariate analysis showed that risk factors have a relationship with the pneumonia is exclusive breastfeeding (OR = 3.714), immunization status (OR = 3.375) and the risk factors associated with pneumonia is not LBW(OR = 0.521).